Effect of microbial cell preparation on renal profile and liver function among type 2 diabetics: a randomized controlled trial - Firouzi, Somayyeh; Mohd-Yusof, Barakatun-Nisak; Majid, Hazreen Abdul; Ismail, Amin; Kamaruddin, Nor Azmi (BMC, 2015)
Background: The beneficial effect of probiotics on renal profile and liver function has been reported among patients with chronic kidney disease and fatty liver respectively. However, its effect on renal profile and liver function among type 2 diabetic individuals has not been fully understood. To investigate the effect of microbial cell preparation on renal profile and liver function tests among type 2 diabetic individuals. Methods: A randomized, double-blind, parallel-group, controlled clinical trial was conducted on a total of 136 type 2 diabetics age 30-70 years old in a teaching hospital in Kuala Lumpur, Malaysia. Subjects were randomly assigned to receive microbial cell preparation (N = 68) or a placebo (N = 68) for 12 weeks. The outcomes measured at baseline, week 6, and week 12 and included changes in renal profile (Sodium, Potassium, Urea, Creatinine, Glomerular Filtration Rate), and liver function tests (Albumin, Total Protein, Alkaline Phosphatase, Alanine Aminotransferase, Aspartate Aminotransferase). Intention to treat (ITT) analysis was performed on all the recruited subjects, while per protocol (PP) analysis was conducted on those who completed the trial with good compliance. Result: The urea levels significantly declined in the probiotic group. Serum urea levels reduced from 4.26 mmol/L to 4.04 mmol/L in Probiotic Group while it increased in Placebo Group from 4.03 mmol/L to 4.24 mmol/L. These changes were significant between groups in ITT analysis (p = 0.018). Other parameters did not change significantly between groups. Conclusion: 12 weeks supplementation with daily dosage of 6 x 10(10) Colony Forming Units of multi-strain microbial cell preparation significantly improved urea levels.